SIGN ANALYSIS OF THE INSTAGRAM USER USING SEMIOTIC CHARLES S. PEIRCE - Farhan Muhammad Ramadhan; Shavira Nisa Delardhi; Ula Nisa El Fauziah (PROJECT (Professional Journal of English Education), 2018)
Sign intentionally produced in order to signify where these signs always originate from a sender. They are formed consciously by someone, based on specific conventions, and with the aim of communicating something to someone. Nowedays, many of the signs used in social media, especially in social media Instagram as one of the popular social media that is not only used for communication but also sometime be a place to share a moment using picture or video. The objective of this research is to find out the intent of sign in the picture that user Instagram share and also analyzed picture to find out the connotation. This research uses descriptive qualitative approach such the researchers analyses the visual signifier and concept of meanings as signified the data with analyzed based on C.Peirce's triadic model of sign which consist of representament, object and interpretant. Researchers use 8 pictures random taken from Instagram user. The result of this research is the researchers find 4 words from the text in the pictures that including to energetic interpretant with the dynamical interpretant process, and also find 4 words from the text in the pictures that including to emotional interpretant with the dynamical interpretant process.